Enhancing the properties of Al–Ni added medium Mn steel by tailoring B2–NiAl precipitates through aging treatment - Sahoo, Biraj Kumar; Srivastava, Vikas Chandra; Chandan, Avanish Kumar; Ghosh Chowdhury, Sandip (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2022)
In the present work, the effect of aging treatment and the role of precipitates in improving the strength-ductility combination of intercritically annealed Fe–8Mn–4Al-3.5Ni-0.6Si-0.2C (wt.%) medium Mn steel has been studied. The steel has been intercritically annealed at 750 °C for 1 h and subjected to two different aging treatments, one-stage aging treatment at 500 °C for 3 h, and two-stage aging comprising first stage at 650 °C for 3 h followed by water quenching and second stage at 500 °C for 3 h. The microstructure, precipitates characteristics, mechanical properties and deformation behavior of the aged samples have been investigated. It was observed that after one-stage and two-stage aging treatment, the strength-ductility product of the steel improved significantly. The one-stage aging led to the formation of nano-sized NiAl precipitates in both ferrite and austenite, which resulted in an increment of yield strength (YS) by 300 MPa, with no notable decrease in ductility, as compared to the intercritically annealed sample. The two-stage aging led to phase-selective precipitation of NiAl of varying sizes in ferrite and austenite during the first and second stages of aging respectively. A combination of TRIP-TWIP effect and precipitation strengthening by the NiAl in austenite phase was observed in the two-stage aged sample, which led to sustained three-stage work-hardening during deformation resulting in improved elongation and strength-ductility combination.